PTSD symptom presentation among people with alcohol and drug use disorders: Comparisons by substance of abuse. (January 2018) - Dworkin, Emily R.; Wanklyn, Sonya; Stasiewicz, Paul R.; Coffey, Scott F.
Abstract: Posttraumatic stress disorder (PTSD) and substance use disorders (SUDs) commonly co-occur, and there is some evidence to suggest that PTSD symptom clusters are differentially related to various substances of abuse. However, few studies to date have compared PTSD symptom patterns across people with different types of SUDs, and fewer still have accounted for the presence of comorbidity across types of SUDs in understanding symptom patterns. Thus, in the current study, we use a treatment-seeking sample of people with elevated symptoms of PTSD and problem alcohol use to explore differential associations between past-year SUDs with active use and PTSD symptoms, while accounting for the presence of multiple SUDs. When comparing alcohol and drug use disorders, avoidance symptoms were elevated in those with alcohol use disorder, and hyperarousal symptoms were elevated in those who had a drug use disorder. In the subsample with alcohol use disorder, hyperarousal symptoms were elevated in people with co-occurring cocaine use disorders and numbing symptoms were elevated in people with co-occurring sedative/hypnotic/anxiolytic use disorder. These findings provide evidence for different symptom cluster patterns between PTSD and various types of SUDs and highlight the importance of examining the functional relationship between specific substances of abuse when understanding the interplay between PTSD and SUDs. Highlights: Treatment-seeking patients with substance use disorders and likely PTSD are sampled. Associations between PTSD symptoms and substance use disorders are tested. Different symptom patterns are identified across types of substance use disorder.